Synthesis of Some New Heterocyclic Fused Rings Compounds Based on 5-Aryl-1,3,4-Oxadiazole - Abbas, Zahra Mohammed; Hussain, Dhuha Faruq; Shakir, Raied Mustafa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The work includes synthesis and characterization of some new heterocyclic compounds, as flow: The compound (3) (5-(4-chlorophenyl) -2-hydrazinyl-1,3,4-oxadiazole was synthesized by using two methods; the first method includes the direct reaction between hydrazine hydrate 80% and 5-(4-chlorophenyl)-2- (ethylthio) 1,3,4-oxadiazole (1), the second method involves converting 5-(4-chlorophenyl)-1,3,4-oxadiazol-2-amine (2) to diazonium salt then reducing this salt to compound (3) by stannous chloride. Compound (3) was used as starting material for synthesizing several fused heterocyclic compounds. The compound 6-(4-chlorophenyl)[1,2.4] triazolo [3,4,b][1,3,4] oxadiazole-3-(2H) thione (compound 4) was synthesized from the reaction of compound (3) with carbon disulfide in presence of potassium hydroxide. Compound 6-(4-chlorophenyl)-[1,2,4] triazolo [3,4-b][1,3,4] oxadiazole-3-amine (5) was synthesized from treatment of compound (3) with cyanogen bromide at room temperature in the presence of sodium hydrogen carbonate. Direct reaction between acetic acid and compound (3) in POCl3 affords 6-(4-chlorophenyl)-3-methyl-[1,2,4] triazolo [3,4,b][1,3,4] oxadiazole (compound 6). Five new fused rings derivatives (12-16) [6-(4-chlorophenyl)-3-(aryl)-[1,2,4] triazolo[3,4-b][1,3,4]oxadiazol] were synthesized by two steps. The first step was synthesized by corresponding Schiff bases (7-11) from reaction compound (3) with five aryl aldehyde. These Schiff bases were used as substrate to synthesize compounds (12-16) by treating these compounds with bromine in glacial acetic acid in dry sodium acetate.The synthesized compounds were characterized by FTIR,H-NMR,C-NMR and CHNS analysis.